Critical analysis of the potential for microRNA biomarkers in breast cancer management - Graveel CR (Dove Medical Press, 2015)
Carrie R Graveel,1 Heather M Calderone,2 Jennifer J Westerhuis,2 Mary E Winn,3 Lorenzo F Sempere21Breast Cancer Signaling and Therapeutics Team, Program in Molecular Oncology and Pre-clinical Therapeutics, Center for Cancer and Cell Biology, 2Laboratory of microRNA Diagnostics and Therapeutics, Program in Skeletal Disease and Tumor Microenvironment, Center for Cancer and Cell Biology, 3Bioinformatics and Biostatistics Core, Program for Technologies and Cores, Van Andel Research Institute, Grand Rapids, MI, USAAbstract: Breast cancer is a complex and heterogeneous disease. Signaling by estrogen receptor (ER), progesterone receptor (PR), and/or human EGF-like receptor 2 (HER2) is a main driver in the development and progression of a large majority of breast tumors. Molecular characterization of primary tumors has identified major subtypes that correlate with ER/PR/HER2 status, and also subgroup divisions that indicate other molecular and cellular features of the tumors. While some of these research findings have been incorporated into clinical practice, several challenges remain to improve breast cancer management and patient survival, for which the integration of novel biomarkers into current practice should be beneficial. microRNAs (miRNAs) are a class of short non-coding regulatory RNAs with an etiological contribution to breast carcinogenesis. miRNA-based diagnostic and therapeutic applications are rapidly emerging as novel potential approaches to manage and treat breast cancer. Rapid technological development enables specific and sensitive detection of individual miRNAs or the entire miRNome in tissues, blood, and other biological specimens from breast cancer patients. This review focuses on recent miRNA research and its potential to address unmet clinical needs and challenges. The four sections presented discuss miRNA findings in the context of the following clinical challenges: biomarkers for early detection; prognostic and predictive biomarkers for treatment decisions using targeted therapies against ER and HER2; diagnostic and prognostic biomarkers for subgrouping of triple-negative breast cancer, for which there are currently no targeted therapies; and biomarkers for monitoring and characterization of metastatic breast cancer. The review concludes with a critical analysis of the current state of miRNA breast cancer research and the need for further studies using large patient cohorts under well-controlled conditions before considering the clinical implementation of miRNA biomarkers.Keywords: miRNA, miR, blood, formalin-fixed paraffin-embedded tissues, diagnostics FFPE tissues